2016
DOI: 10.18235/0000545
|View full text |Cite
|
Sign up to set email alerts
|

Engine of Growth?: The Caribbean Private Sector Needs More Than an Oil Change

Abstract: ative Commons IGO 3.0 Attribution-NonCommercial-NoDerivatives (CC-IGO BY-NC-ND 3.0 IGO) license (http://creativecommons.org/licenses/by-nc-nd/3.0/igo/legalcode) and may be reproduced with attribution to the IDB and for any non-commercial purpose.No derivative work is allowed.Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for attribution, and the use of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Ruprah and Sierra (2016) found that these complaints are generally correlated with objective indicators and reflect a reality faced by private firms in the Caribbean.…”
Section: Microeconomic Constraintsmentioning
confidence: 83%
See 1 more Smart Citation
“…Ruprah and Sierra (2016) found that these complaints are generally correlated with objective indicators and reflect a reality faced by private firms in the Caribbean.…”
Section: Microeconomic Constraintsmentioning
confidence: 83%
“…In order to assess performance at the firm level, two indicators are used: sales growth and TFP. Both measures are calculated for the 12 Caribbean countries that were covered in the Productivity, Technology and Innovation (PROTEqIN) Survey (Ruprah and Sierra 2016).…”
Section: Performance Of Firmsmentioning
confidence: 99%
“…A 10 percent reduction in crime is associated with an 8 percent increase in sales growth for firms that are tourism dependent and a 4 percent increase in sales growth in commodity-dependent countries. Thus, the tourism-dependent economies 9 See Ruprah and Sierra (2016) for further details. Group,195,197,222 airlift from, 50, 51f, 52n10 CBRs and,274,282,285 Cuba and,3,5,46,59,[63][64][65][66][67][68][69][70][71][72][73][74][75]68f,69n5 …”
Section: The Economic Impact Of a Reduction In Crimementioning
confidence: 99%
“…The findings of these initiatives are detailed in three recent IDB publications (Ruprah and Sierra 2016;Sutton and Ruprah 2017;Jaitman 2017). This chapter summarizes some of the main findings of these publications, with a preliminary assessment of their possible implications.…”
mentioning
confidence: 97%
“…Some researchers and policymakers have argued that the Caribbean's private sector should play a key role in promoting higher and more sustainable growth. However, the private sector in the Caribbean is currently characterised as being largely static and underperforming based on estimates of sales growth and total factor productivity (Ruprah and Sierra 2016).…”
Section: Introductionmentioning
confidence: 99%